2012
DOI: 10.1590/s0100-72032012001000002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of common mental disorders in women with polycystic ovary syndrome and its relationship with body mass index

Abstract: PURPOSE: To evaluate the prevalence of common mental disorders in women diagnosed with polycystic ovary syndrome as compared with paired controls without this syndrome. METHODS: Cross-sectional study with a Control Group examining women between the ages of 18 and 30 who did not use antidepressants and who sought the Gynecology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…31 Benzer şekilde Rodrigues ve ark.nın PKOS hastalarında BKİ değişikliklerinin mental rahatsızlıklar ile ilişkisini araştırdıkları ça-lışmalarında, PKOS hastalarında 3 kat artmış psikolojik rahatsızlık insidansı saptamış olmakla birlikte, bu değişikliklerin BKİ'den bağımsız olduğu sonucuna varmışlardır. 32 Çalışmamızın en önemli kısıtlaması hasta sayısının rölatif olarak düşük ve güç analizinin yapılmamış olmasıdır. Her ne kadar hasta ve kontrol grubu sayımız istatistiksel olarak anlamlı bir sonuca varmak için yeterli olsa da daha yüksek hasta sayısı çalışmamızın istatistiksel gücünü kesin bir şekilde artıracaktır.…”
Section: Discussionunclassified
“…31 Benzer şekilde Rodrigues ve ark.nın PKOS hastalarında BKİ değişikliklerinin mental rahatsızlıklar ile ilişkisini araştırdıkları ça-lışmalarında, PKOS hastalarında 3 kat artmış psikolojik rahatsızlık insidansı saptamış olmakla birlikte, bu değişikliklerin BKİ'den bağımsız olduğu sonucuna varmışlardır. 32 Çalışmamızın en önemli kısıtlaması hasta sayısının rölatif olarak düşük ve güç analizinin yapılmamış olmasıdır. Her ne kadar hasta ve kontrol grubu sayımız istatistiksel olarak anlamlı bir sonuca varmak için yeterli olsa da daha yüksek hasta sayısı çalışmamızın istatistiksel gücünü kesin bir şekilde artıracaktır.…”
Section: Discussionunclassified
“…Generalised mental wellbeing on the other hand was defined, as having both depression and anxiety, use of medication for psychiatric disorders as reported within the studies, self-reported MH symptoms, or reported under the term “common mental health” (CMH) by a study authors based on scales such as SF-36. 4244…”
Section: Methodsmentioning
confidence: 99%
“…Generalised mental wellbeing on the other hand was defined, as having both depression and anxiety, use of medication for psychiatric disorders as reported within the studies, self-reported MH symptoms, or reported under the term "common mental health" (CMH) by a study authors based on scales such as SF-36. [42][43][44] A Random-effects models were used to calculate overall summary estimates of anxiety, depression, and CMH in PCOS patients. 45 The routine "metaprop" of the software STATA's (V.16) which provides pooled summary of proportions and 95% confidence intervals based on Newcombe exact binomial estimation was used.…”
Section: Statistical Analysis Planmentioning
confidence: 99%
“…Pcos creates an important psychological burden throughout the life-time of these women [ 9 , 10 , 19 ]. It has been reported that 57% of women with polycystic ovary syndrome have at least one mental disorder [ 20 ]. High levels of androgens, acne, infertility and fear of it, hirsutism, high body mass index, low body image, sexual problems and coping with the disease impair the mental health of them [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In PCOS, symptoms and co-morbidities increase the risk of adverse psychological health consequences. While, mental health is particularly related to the management of polycystic ovary syndrome and is an essential component of self-efficacy and enjoying a healthy lifestyle [ 20 , 25 ]. Lifestyle modification is the priority in the management of polycystic ovary syndrome, since small changes in these women’s lifestyle and a balanced weight, can improve symptoms, and increase ovulation and improve fertility [ 6 , 26 ].…”
Section: Introductionmentioning
confidence: 99%